Peter Doherty on poultry genetics and the importance of eggs in African diets - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, speaks on ILRI's work on poultry and eggs, supported by the Bill & Melinda Gates Foundation. Filmed in September 2016.